Prevalence and influencing factors of spirometry examination among residents aged 40 years and older in Inner Mongolia Autonomous Region - a cross-sectional survey - Huimin LIU; Min ZHANG; Wenjie CHEN; Liying QIAO; Yonggang QIAN; Chunxia HUI (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo examine the prevalence and influencing factors of spirometry examination among residents aged ≥ 40 years in Inner Mongolia Autonomous Region (Inner Mongolia) for promoting prevention and control of chronic respiratory diseases. MethodsUsing multistage stratified cluster and probability proportionate to size sampling and a questionnaire adopted by Chinese Center for Disease Control and Prevention, we conducted a face-to-face survey among 2 400 permanent residents aged ≥ 40 years in four prefectures/banners with chronic obstructive pulmonary disease surveillance project in Inner Mongolia during May - December 2019. The estimated prevalence of spirometry examination in the participants was calculated based on complex sampling weight design; the impact factors of spirometry examination were explored with unconditional multivariate logistic regression analysis. ResultsOf the 2302 participants with eligible responses, 142 reported ever having pulmonary function test. The complicated weighted proportion of spirometry examination was 5.1% for the population surveyed. The results of logistic regression analysis showed that the residents with the education of junior high school and above, being enterprise clerks or professional and technical personnel in enterprises, being workers not classified or being unemployed, being aware of the names of respiratory diseases, ever suffering from respiratory symptoms, and with the history of respiratory illness were more likely to have spirometry examination; while the female residents were less likely to have the examination. ConclusionThe proportion of ever having spirometry examination was relatively low and mainly influenced by gender, education, occupation, the awareness of respiratory disease, respiratory symptoms, and the history of chronic respiratory disease among residents 40 years old and older in Inner Mongolia.